The Influence of Professional Ethics, Self Efficacy and Love of Money on Accounting Students' Interests in a Career in Taxation with Motivation as a Moderating Variable (Study on Accounting S1 Students at Muhammadiyah University of Sidoarjo) - Leny Aisyah; Santi Rahma Dewi (Journal of Islamic and Muhammadiyah Studies, 2023)
This study aims to determine the effect of professional ethics, self-efficacy and love of money on the interest of accounting students in a career in taxation, whether motivation is able to moderate professional ethics, self-efficacy and love of money onrthe interestjof accountingjstudents inja careerjinjtaxation. Thisjresearch method usesjquantitative,jdata collection is done by distributing questionnaires. The population in this study were students of the 2018 accounting study program. The sampling technique used in this study was using the Slovin formula as many as 55 respondents. The data analysis technique used in this research is using the SPSS Verssion 26 application.The results showed that (1) professional ethics and love of money had a significant effect on the interest of accounting students in a career in taxation, (2) Self Efficacy had no significant effect on the interest of accounting students in a career in taxation, (3) motivation was able to moderate professional ethics and love of money on the interest of accounting students in a career in taxation, (4) motivation is not able to moderate self-efficacy on the interest of accounting students in a career in taxation.